Determinants and sources of iron intakes of australian toddlers: Findings from the SMILE cohort study - Scott, Jane; Gee, Georgina; Devenish, Gemma; Ha, D.; Do, L. (Molecular Diversity Preservation International (MDPI), 2019)
© 2019 by the authors. Licensee MDPI, Basel, Switzerland. The first two years of life is a period of rapid growth and development. During this time a lack of key nutrients, including iron, can have long-lasting effects on motor and cognitive performance. The purpose of this cross-sectional study was to determine intake and sources of iron in a cohort of 828 toddlers (mean age; 13.1 mo) participating in the Adelaide-based Study of Mothers’ and Infants’ Life Events affecting oral health (SMILE), and to identify determinants of iron intake. At approximately 12 months of age, 3 non-consecutive days of dietary intake data were collected using a 24-h recall and 2-days food record. The Multiple Source Method was used to combine data from the 24-h recall and each day of the food record to estimate usual iron intake and descriptive statistics were used to report sources of iron. Linear regression was used to identify associations between iron intake and non-dietary determinants (maternal age, education, country of birth, BMI, socioeconomic position, parity, toddler sex) and primary milk feeding method at 12 months. The mean intake of iron was 7.0 (95% CI 6.7–7.2) mg/day and 18.2% of children had usual intakes below the estimated average requirement of 4 mg/day. The main sources of iron included infant and toddler cereals and formulas. Milk feeding method and parity were significantly associated with iron intake. Toddlers with siblings and those who received breast milk as their primary milk feed had significantly lower iron intakes than only children and those who received formula, respectively. The Australian Infant Feeding Guidelines promote the importance of iron-iron-rich complementary foods such as meat and meat alternatives. However, low intakes of this food group suggest that parents do not recognize the importance of these foods or understand the specific foods that toddlers should be eating.